Underwater Wireless Optical Communication (UWOC) - Bayan Shtaiwi; Hadeel Masri; Mayson Alawneh (My University, 2025)
Underwater wireless communication refers to transmitting data in unguided water environment through the use of wireless carriers, i.e., radio frequency wave, acoustic wave, and optical wave. We focus, in this thesis, on the underwater wireless optical communication (UWOC) that employs optical wave as the transmission carriers. I n comparison to RF and acoustic counterparts, UWOC has a much higher transmission bandwidth, thus providing much higher data rate. Due to this high speed transmission advantage, UWOC has attracted considerable attention in recent years. Many potential appl ications of UWOC systems have been proposed for environmental monitoring, offshore exploration, disaster precaution, and military operations. However, UWOC systems also suffer from severe absorption and scattering introduced by underwater channel. In order to overcome these technical challenges, several new system design approaches, which are different from the conventional terrestrial free space optical communication, have been explored in recent years.